The influence of leadership and work motivation on employee discipline at PT Datascript Indonesia - Timbang, Erwin; Saputra, Bobby W. (International Journal Labs, 2024)
This study aims to analyze the influence of leadership and work motivation on employee work discipline at PT Datascript Indonesia. The study's population consisted of 1,045 employees, with a sample of 289 employees determined using the Slovin formula. Data collection was conducted through questionnaires and documentation, utilizing an incidental sampling method. The results of the study showed that leadership in this company is included in the good category, with an average respondent response of 3,887 from 13 statement items. Work motivation has a significant positive influence on the work discipline of the workforce (p 0.05). Multivariate linear regression analysis shows that both leadership and workplace motivation have a positive impact on work discipline simultaneously. The findings of this study are expected to provide additional information about the relationship between leadership, work motivation, and work discipline, as well as provide useful insights for employees at Datascript, so that it can improve the company's performance and achieve its strategic goals.